FENOMENA BANKONKA PADA MASYARAKAT JEPANG YANG TERCERMIN DALAM DRAMA SERIAL KEKKON DEKINAI OTOKO KARYA OZAKI MASAYA - Arianie, Ervina Yuni (Jurnal Ilmiah Mahasiswa FIB, 2013)
This paper studies discusses the phenomenon of postponing marriage (bankonka) in Japanese society that continues today. In this study the author used data source in the form of a serial drama entitled Kekkon Dekinai Otoko. This serial drama tell the story of Shinsuke Kuwano, a 40 years old man who works as an architect but not married. Yet in this serial drama a lot of bankonka phenomenon reflected in the Japanese society. Therefore, the author will answer the problem of this study is, "how bankonka phenomenon that is reflected in the serial drama Kekkon Dekinai Otoko?". The reason is the main character and a supporting actress that postponing marriage and public opinion around them will be researched by comparing it to the reality and the view of the Japanese people respond of bankonka in real life according to the results of scientific research on bankonka.   This study use the approach of sociology literature from Ian Watt, the literature as a reflection of society. This approach to analyze the phenomenon of bankonka in serial drama Kekkon Dekinai Otoko, and with the theory of mise-en-scene use as supporting theory in this. Analyses were performed with picture and figures of Hayasaka and Shinsuke in the form of dialogues and scenes in the serial drama.   These results indicate that there are 27 scenes and dialogue that reflect bankonka phenomenon. Dialogues and scenes showing the same reasons of postponing marriage in the reality of Japanese society. The cause of bankon in serial drama are, change in views on marriage, the rejection of miai (matchmaking) and a tendency to choose a partner based on ren ai (love). As a result, make their increasing MAFM (Mean Age at First Marriage) Japan.   The author suggest that further research, could use a sociological approach to research literature on shousika or koureika shakai as the impact of bankonka. As for learning Japanese culture and literature students should be more critical in the enjoyment of literature, film and Japanese drama series that can be used as a source of knowledge about the phenomenon of cultural and social phenomena that exist in Japan.   Key Word: serial drama, phenomenon, bankonka, Japanese society.